Cultura tributaria y formalización de los comerciantes de celulares y accesorios de la ciudad de Contamana año 2022 - López Inuma, Elena Emerita (2022)
The general objective of the research was to determine the relationship between the tax culture and formalization of cell phone and accessory sales merchants in the city of Contamana Año 2022., where an applied type study, correlational level and non-experimental design was used, made up of a population of 83 merchants, the survey technique was applied to them and the question questionnaire as an instrument. It was concluded that the tax culture is rated as average by 25%, because they sometimes contribute to investments managed by the state by paying their taxes, and almost always the costs for registering the company are accessible, and almost always The collecting entity carries out campaigns to encourage the payment of taxes. On the other hand, the formalization is qualified as average by 27% because sometimes they have knowledge about the natural or legal person, but almost never under which tax regime is the commercial activity of their business, while sometimes the businesses have operating license, and the staff that works in your business is registered on the payroll. Likewise, it has been determined that there is a significant relationship between tax culture and formalization of merchants, which has been contrasted by a correlation coefficient of 0.831, being a considerable positive level and significance (bilateral) of 0.000.